Pellino-1 Regulates Immune Responses to Haemophilus influenzae in Models of Inflammatory Lung Disease - Hughes, Bethany M.; Burton, Charlotte S.; Reese, Abigail; Jabeen, Maisha F.; Wright, Carl; Willis, Jessica; Khoshaein, Nika; Marsh, Elizabeth K.; Peachell, Peter; Sun, Shao C.; Dockrell, David H.; Marriott, Helen M.; et al. (Frontiers in Immunology, 2019)
Nontypeable Haemophilus influenzae (NTHi) is a frequent cause of lower respiratory tract infection in people with chronic obstructive pulmonary disease (COPD). Pellino proteins are a family of E3 ubiquitin ligases that are critical regulators of TLR signalling and inflammation. The aim of this study was to identify a role for Pellino-1 in airway defence against NTHi in the context of COPD. Pellino-1 is rapidly upregulated by LPS and NTHi in monocyte-derived macrophages (MDMs) isolated from individuals with COPD and healthy control subjects, in a TLR4 dependent manner. C57BL/6 Peli1-/- and wild-type (WT) mice were subjected to acute (single LPS challenge) or chronic (repeated LPS and elastase challenge) airway inflammation followed by NTHi infection. Both WT and Peli1-/- mice develop airway inflammation in acute and chronic airway inflammation models. Peli1-/- animals recruit significantly more neutrophils to the airway following NTHi infection which is associated with an increase in the neutrophil chemokine, KC, in bronchoalveolar lavage fluid as well as enhanced clearance of NTHi from the lung. These data suggest that therapeutic inhibition of Pellino-1 may augment immune responses in the airway and enhance bacterial clearance in individuals with COPD.